ON THE WAYS OF EXISTENCE AND PRESERVATION OF MUSICAL TRADITIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The object of the article is musical cultures (traditions) as a phenomenon. Its subject is the qualitative differences of musical cultures in terms of their attitude to tradition and their typology. Therefore, the title of the article, «On the Ways of Existence and Preservation of Musical Traditions,» also serves as a statement of the goal. Based on the study of the state of European and non-European musical traditions, the article provides conclusions on the ways of their existence (authentic, preserved, transplanted, and transformed) and, most importantly, their maintenance and preservation. The article highlights the fundamental difference between the European musical tradition and the rest of the world’s traditions. Unlike traditional cultures, European music has become much more separate from everyday life, which has created conditions for the autonomy of music, the extraterritoriality and super-ethnicity of the tradition itself, and its spread around the globe, along with the spread of industrial bourgeois civilization. In traditional societies, all artistic and at the same time musical traditions develop naturally, and there is no need for special efforts to preserve them. The modern global world is a conglomeration of societies of various types. Despite examples of greater or lesser isolation, traditional societies and cultures are still connected to and often «immersed» in industrial societies. Therefore, the problem of preserving traditional cultures is a problem of interaction between different types of cultures, and it is important for us to understand their characteristics and differences. Among the new results of the work are a typology of the ways in which musical traditions exist, as well as the conclusion that the main means of maintaining the traditions of the past in modern conditions is historical research in musicology and its practical implementation.
Keywords: musical tradition, traditional culture, non-traditional culture, preservation, transplantation, transformation.